The role of salivary caffeine clearance in the diagnosis of chronic liver disease - Anurag Tripathi; Brijesh Tiwari; Ranjit Patil; Vikram Khanna; Vandana Singh (Journal of Oral Biology and Craniofacial Research)
Background: Chronic liver diseases (CLD) are quite prevalent throughout the globe. Its early and correct diagnosis is always a concern among physicians, especially the residual liver function. For this various substrates like caffeine are being investigated in body fluids like serum and saliva. Saliva as a study sample has its own advantages due to its non invasiveness; it can be very useful study sample. Methods: 30 Subjects with CLD and 15 healthy controls were administered 200 mg of caffeine. Subjects classified into severity groups (class-A-mild-n = 9, B-moderate-n = 11, and C-severe-n = 10) based on “Child-pugh classification” of severity of liver disease. After 17 h of dietary caffeine restriction and before drug administration, 0 h salivary sample was taken. After the dose of caffeine, 4 and 16 h saliva sample was taken. Blood sample was taken from controls only at same time points. These samples were analyzed on semi automated analyzer using Enzyme Multiplied Immunoassay Technique (EMIT) by spectrophotometric method. Caffeine clearance values were calculated and results were statistically analyzed. Results: Significant correlation was found between serum caffeine clearance and salivary caffeine clearance (SCC). Controls showed higher mean of SCC value of 1.6 ± 0.2 ml/min/kg while SCC values of subjects were less, with mean of 0.5 ± 0.2 ml/min/kg. Significant correlation was found between degree of hepatic dysfunction and SCC values. Conclusion: Saliva can be used for diagnosis of CLD and assessment of residual liver function in CLD as alternative to serum.